Bond Strength Evaluation of Waterproofing Membrane Assembly in Concrete Bridges - Khalayleh, Yahia A. S.; Al-Asi, Aya; Asi, Ibrahim; Alawadi, Roaa (Civil Engineering Journal, 2025)
On the concrete bridge decks overlaid by HMA, slippage cracks usually appear on the HMA layer because of the presence of waterproofing membranes below the HMA layer and a lack of bonding of the membrane with the PCC underlying layer. The objective of this work is to develop a laboratory-based method for the fabrication of test samples of an HMA layer, waterproofing membrane, and PCC layer system. In addition, a bond strength test procedure was adapted to evaluate the bonding of the three layers assembly at different test temperatures in the laboratory prior to the field application. According to the obtained evaluation results, it was found that the weakest bond in the HMA, waterproofing membrane, and PCC assembly is the bond between the HMA layer and the waterproofing membrane. The bond strength of the assembly is highly affected by increasing temperature, since it lost approximately 75% of its strength when the test temperature increased from 25°C to 50°C. Likewise, as the test temperature increased from 25°C to 60°C, the assembly lost approximately 75% of its strength. Therefore, the bond strength should be evaluated at the expected pavement temperature in the field, specifically at the membrane interface level. Doi: 10.28991/CEJ-2025-011-02-010 Full Text: PDF